THE EFFECT OF GROSS DOMESTIC PRODUCT AND INTEREST RATES ON CREDIT DEMAND - Saputri, Erliana Eka (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
In Indonesia, bank banking is very meaningful for example in terms of development. This is becausebanks can influence the overall economic cycle. The increase in demand for bank credit has resulted inincreased purchasing power, increased business enthusiasm and an investment bonus. Which inconclusion will produce the Multiplier Effect. The multiplier effects include the addition of newbusiness establishments, additional workforce, increased demand for raw materials, increasedproduction output and increased purchasing power which will affect future economic growth. Theresearch has the objective of explaining the Effect of Gross Domestic Product and Interest Rates on CreditDemand. This research uses descriptive quantitative research methods and uses multiple regression whichcan see the effect of Gross Domestic Product and Interest Rates on Credit Demand. In this study, itwas found that the Gross Domestic Product has an influence on the demand for credit, while the interestrate has no influence on the demand for credit.